Single mode ridge waveguide using hybrid organic inorganic sol gel [electronic resource] - Amirjan Nawabjan, 1986- (2012)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2012